PCI Prototyping Platform. - Garcia, Richard T. (Philippine Engineering Journal)
Peripheral Component Interconnect or PCI, a high speed bus technology is being considered as superior to other bus technologies when it comes to design and performance. Different adapters, which need fast accesses with one another or with system memory, can be connected to the PCI bus with the clock frequency approaching the processor's full speed. The stringent electrical, functional and timing specifications of PCI make it a formidable design challenge. A flexible PCI solution is needed to meet the current and the future requirements. Using a Very High Speed Integrated Circuit Hardware Description Language (VHDL) and Xilinx Field Programmable Gate Array (FPGA) Technology, a PCI prototyping platform card can be developed. The PCI prototyping platform card will be implemented using PCI 32 bit wide bus implementation with a clock frequency of 33 MHz. This card is capable of performing read and write transactions. Three registers will be provided for prototyping purposes. It is here where data can be read and written. The PCI prototyping platform card will be designed using VHDL and will be implemented using Xilinx FPGA technology. It is the objective of this project to develop and implement a PCI prototyping platform card capable of performing read and write transactions which will serve as a benchmark for future PCI based projects.